Design and characteristic evaluation of a high-speed CMOS imaging system. (16th November 2010) - Shang, Yuanyuan; Guan, Yong; Liu, Xumin; Zhang, Weigong
This paper introduces the design of a high-speed 2K × 2K Complementary Metal-Oxide-Semi-Conductor (CMOS) camera, which is part of the Wide Field Monitor System proposed in China recently. It consists of an analogue and a digital embedded system integrated with a NIOS II soft-core processor serving as the control and data acquisition system. Research on characteristic measurement for CMOS imagers, including readout noise, linearity, Quantum Efficiency (QE), photo response non-uniformity, dark current, full-well capacity and gain, was also carried out. The evaluation results indicate that this high-speed CMOS camera can meet the requirements of the Wide Field Monitor System.